SAFE-PEDRUG: A NEW STRATEGY FOR PAEDIATRIC DRUG RESEARCH. Issue 1 (14th December 2015) - Bruyne, Pauline De; Meesters, Kevin; Walle, Johan Vande
Abstract : Background: Drug evaluation in children is stimulated by initiatives of the Regulatory Authorities; in Europe by the 'Paediatric Regulation'. As stated in this Regulation, Paediatric Investigational Plans must be submitted to the Paediatric Committee around the end of Phase I adult trials. However, the proposed paediatric trials tend to be amended frequently and postponed to the end of the drug evaluation process, as they are largely based on extrapolations of results of adult trials. Materials and methods: Experts in paediatrics, pharmaceutical sciences, veterinary medicine and ethics (of three Belgian universities) collaborated to develop a research consortium that will focus mainly on generating paediatric pharmacokinetic and pharmacodynamic (PK/PD) knowledge before the actual human trials are performed. National and international stakeholders (including Industry, Regulatory Authorities, and Patient Organisations) support this consortium in the valorisation of results. Results: The above-mentioned networking resulted in the SAFE-PEDRUG project, funded by the Agency for Innovation by Science and Technology (Flanders). This program will explore the value of the porcine juvenile animal model and PK modelling (physiologically-based pharmacokinetic modelling) in providing prior paediatric PK/PD-knowledge. For the evaluation of this approach, three case compounds were selected: desmopressin, lisinopril, and fluoroquinolones. The results of the models are plotted against human paediatric data. Furthermore, PK/PD in neonates and critically ill children will also be explored. Conclusion: A close collaboration of experts and stakeholders is mandatory for the future of paediatric pharmacology. Exchange of ideas and knowledge can help to tailor paediatric clinical trials to the PK/PD-characteristics and needs of children.